2014
DOI: 10.1080/10888438.2014.973028
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Processing and Word Reading in Typically Developing and Reading Disabled Children: Severity Matters

Abstract: In this study word reading (WR) fluency was used to dichotomously classify 1,598 Dutch children at different cutoffs, indicating (very) poor or (very) good reading performance. Analysis of variance and receiver operating characteristics were used to investigate the effects of rapid automatized naming (RAN) and phonemic awareness (PA) in predicting group membership. The highest predictive values were found for the combination of RAN and PA, particularly for the poorest readers. Furthermore, results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…There was some evidence in the individual quantile regressions that phonological awareness was more strongly related to reading at the lower quantiles (Figures and ); however, the multiple quantile regressions for kindergarten showed a more consistent pattern across quantiles (Figure ). The pattern of collinearity with the other predictors may have contributed to this and makes direct comparison with other studies more difficult, especially those that did not include measures of letter knowledge (de Groot et al, ; Torgesen et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…There was some evidence in the individual quantile regressions that phonological awareness was more strongly related to reading at the lower quantiles (Figures and ); however, the multiple quantile regressions for kindergarten showed a more consistent pattern across quantiles (Figure ). The pattern of collinearity with the other predictors may have contributed to this and makes direct comparison with other studies more difficult, especially those that did not include measures of letter knowledge (de Groot et al, ; Torgesen et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, estimates of predictive relationships will be most representative of readers with average scores within a subgroup, while readers close to the cut-off score will not be well represented. One recent study that addressed the issue of a single cut point among children with varying levels of word reading ability was conducted by de Groot et al (2015). The researchers examined the predictive relationships of phonological awareness and RAN to word reading, using data from a large sample of Dutch children ages 7-14 years.…”
Section: Implications For Theory Policy and Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this predictive relationship appears to remain through adulthood, with correlations as high as r = .53 for adults aged 36–65 (Van den Bos, Zijlstra & lutje Spelberg, 2002). In addition, studies have suggested that 60% to 75% of individuals with reading disabilities exhibit RAN deficits (de Groot, van den Bos, Minnaert, & van der Meulen, 2015; Katzir, Kim, Wolf, Morris & Lovett, 2008; Waber, Forbes, Wolf & Weiler, 2004; Wolf et al, 2002). These strong relationships, which hold across languages (Georgiou et al, 2008; Georgiou, Aro, Liao, & Parrila, 2015; Moll, Ramus, Bartling, Bruder, Kunze et al, 2014; Tan et al, 2005), together with the clinical efficiency of the task itself, which takes less than 5 minutes to administer, make understanding the causal underpinnings of the RAN-reading association a significant goal.…”
mentioning
confidence: 99%